2007
DOI: 10.1300/j115v26n02_01
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Integration of AAMC Medical Informatics Objectives into the Medical School Curriculum

Abstract: The School of Medicine at the Medical College of Virginia Campus of Virginia Commonwealth University examined the 2005/2006 medical school curriculum to ensure that students were prepared to meet the informatics objectives put forward by the AAMC Medical School Objectives Project published in 1998. The AAMC Medical Informatics Objectives Survey, issued in 2005, led the VCU School of Medicine to investigate the points of integration between informatics objectives and course syllabi for the first three years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Most of the studies (22/34, 65%) were published between 2010 and 2019 and were uncontrolled before-and-after studies (24/34, 71%). Other study designs reported in the included studies were case studies (5/34, 15%) [4,[36][37][38][39], controlled before-and-after studies (4/34, 12%) [19,[40][41][42], and a quasi-RCT (1/34, 3%) [43].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the studies (22/34, 65%) were published between 2010 and 2019 and were uncontrolled before-and-after studies (24/34, 71%). Other study designs reported in the included studies were case studies (5/34, 15%) [4,[36][37][38][39], controlled before-and-after studies (4/34, 12%) [19,[40][41][42], and a quasi-RCT (1/34, 3%) [43].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the 34 included studies, 17 (50%) focused on medical informatics [4,18,37,39,40,[42][43][44][45][46][47][48][49][50][51][52][53], 8 (24%) on EHR skills [3,19,41,[54][55][56][57][58], 3 (9%) on computer literacy [59][60][61], 3 (9%) on telemedicine [36,62,63], 2 (6%) on basic programming [38,64], and 1 (3%) on mobile health (mHealth) [65]. Most of the studies (20/34, 59%) were conducted in the United States [3,18,19,39,41,[44][45][46][47][51][52][53][54][55][56][57]…”
Section: Digital Health Courses' Scope Students and Settingsmentioning
confidence: 99%
See 3 more Smart Citations